Dermoscopic Characteristics of Cutaneous Lupus Erythematosus According to Subtype, Lesion Location, Lesion Duration, and CLASI Score - Yıldız Gürsel Ürün; Mustafa Ürün; Mehmet Şerif Danışman (Mattioli1885, 2024)
Introduction: Dermoscopic findings are used to diagnose and evaluate disease activity in patients with cutaneous lupus erythematosus (CLE). Objectives: This study aimed to characterize the dermoscopic features of discoid LE (DLE) and LE tumidus (LET) by lesion duration and CLE Disease Area and Severity Index (CLASI) scores and to examine the dermoscopic findings of lesions in different locations in DLE patients. Methods: Dermoscopic findings (follicular features, perifollicular surface, interfollicular features, and vessel pattern) were assessed and lesion duration (≤12 and >12 months) and CLASI scores (grouped as mild or moderate) were calculated. DLE lesion locations were categorized as, non-scalp, scalp and lip. Results: Forty-eight dermoscopic images from 35 DLE and 4 LET patients were analyzed.  The most common dermoscopic findings in non-scalp DLE were follicular keratotic plugs (82.8%) and white scales (69%). In scalp DLE (n=9), the most common findings were absent follicular openings (77.8%), white structureless areas (77.8%), and perifollicular scaling (66.7%). All LET patients had pink-white background and linear vessels. Follicular plugs, peripheral pigmentation, and polymorphous vessels were lower in patients with mild CLASI activity than moderate activity (P = 0.036, 0.039, and 0.019, respectively). Fibrotic white dots, honeycomb pigment pattern, and blue-gray dots/globules were lower in those with mild CLASI damage scores than moderate damage (P = 0.010, 0.010, and 0.020, respectively). Peripheral pigmentation was more common in patients with lesion duration ≤12 months, while blue-gray dots/globules were more common with lesion durations >12 months. Conclusions: Certain dermoscopic features may facilitate the differential diagnosis of DLE and LET.